A taxonomic monograph of Ipomoea integrated across phylogenetic scales - Muñoz Rodríguez, P.; Carruthers, T.; Wood, J.R.I.; Williams, B.R.M.; Weitemier, K.; Kronmiller, B.; Goodwin, Z.; Sumadijaya, A.; Anglin, Noelle L.; Filer, D.; Harris, D.; Rausher, M.D.; et al. (Springer, 2019)
Taxonomic monographs have the potential to make a unique contribution to the understanding of global biodiversity. However, such studies, now rare, are often considered too daunting to undertake within a realistic time frame, especially as the world’s collections have doubled in size in recent times. Here, we report a global-scale monographic study of morning glories (Ipomoea) that integrated DNA barcodes and high-throughput sequencing with the morphological study of herbarium specimens. Our approach overhauled the taxonomy of this megadiverse group, described 63 new species and uncovered significant increases in net diversification rates comparable to the most iconic evolutionary radiations in the plant kingdom. Finally, we show that more than 60 species of Ipomoea, including sweet potato, independently evolved storage roots in pre-human times, indicating that the storage root is not solely a product of human domestication but a trait that predisposed the species for cultivation. This study demonstrates how the world’s natural history collections can contribute to global challenges in the Anthropocene.